5G‐Hander: A network service for handover detection in 5G networks. Issue 4 (23rd June 2019) - Grasso, Christian; Schembra, Giovanni
Abstract : In the next Fifth Generation (5G) networks, Telco Operators will assign network slices to their users and will guarantee very stringent requirements even in mobility. In this context, detecting handover events will be challenging in order to design management and orchestration policies allowing resource allocation and network slice assignment dynamically. To this purpose, this letter proposes a network service called 5G‐Hander that enables the Network Orchestrator to be alerted of an incoming handover before it is completed, in order to decide resource reallocation or even to inhibit its occurrence. Numerical results show how the proposed network service works in a little, but realistic, network.